Implementing an innovated preservation technology: The American Society of Transplant Surgeons' (ASTS) Standards Committee White Paper on Ex Situ Liver Machine Perfusion. Issue 8 (16th June 2018) - Quintini, Cristiano; Martins, Paulo N.; Shah, Shimul; Killackey, Mary; Reed, Alan; Guarrera, James; Axelrod, David A.; ,
Abstract : The pervasive shortage of deceased donor liver allografts contributes to significant waitlist mortality despite efforts to increase organ donation. Ex vivo liver perfusion appears to enhance preservation of donor organs, extending viability and potentially evaluating function in organs previously considered too high risk for transplant. These devices pose novel challenges for organ allocation, safety, training, and finances. This white paper describes the American Society of Transplant Surgeons' belief that organ preservation technology is a vital advance, but its use should not change fundamental aspects of organ allocation. Additional data elements need to be collected, made available for organ assessment by transplant professionals to allow determination of organ suitability in the case of reallocation and incorporated into risk adjustment methodology. Finally, further work is needed to determine the optimal strategy for management and oversight of perfused organs prior to transplantation. Abstract : The ASTS Standards Committee presents a guidance document to inform the incorporation of liver perfusion technology into clinical liver transplant practice worldwide.